An ABC of tree planting - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Propagating and planting trees. CTA-Agromisa co-publication. 1998. 79 pp. ISBN 90 72746 78 3 CTA number 903, 5 credit points